A Framework for Developing a Hybrid Investment Casting Process - Kumar, Parlad; Singh, Rupinder; IPS Ahuja (Asian Review of Mechanical Engineering, 2013)
Traditionally, the process of investment casting is used for making complex components. But, investment casting is considered economical only when the production volume is high enough. If only limited numbers of pieces are promptly required such as in making prototypes, design iterations and design optimisations the investment casting process proves to be very costly due to time and tooling cost for making dies for producing wax patterns. In such situations, the rapid prototyping technologies are considered very useful as these can produce the patterns with good accuracy and without the necessity of costly hard tooling. The fused deposition modeling (FDM) is one of the rapid prototyping technology that can use plastic material, which can be effectively used for making patterns for investment casting. This combination of the traditional investment casting process with the modern rapid prototyping technologies to obtain a new process may be termed as hybrid investment casting. This study is intended to develop a framework for developing a hybrid investment casting process for industrial applications. For this newly developed process, various process parameters, their control and effects have been represented to obtain the desirable mechanical and metallurgical properties of the castings.